Reprogramming the immunosuppressive breast cancer microenvironment: integrating cellular, metabolic, and stromal targets for rational immunotherapy - Ma, Chang; Teoh, Hoon Koon; Zhao, Yang; Wang, Yifan; Zhao, Jun; Liu, Yan; Zhao, Chen; Ong, Hooi Tin (Frontiers in Immunology, 2026)
Breast cancer, a highly heterogeneous malignancy and a leading cause of cancer-related mortality among women worldwide, is profoundly shaped in its initiation, progression, and therapeutic response by the tumor immune microenvironment (TIME). This review consolidates recent advances in deciphering the cellular, molecular, and metabolic complexity of breast cancer TIME and highlights mechanisms of immune suppression that impede durable treatment efficacy. We critically appraise current and emerging immunotherapeutic approaches, with a focus on strategies that aim to transform immunologically “cold” tumors into “hot,” immune-responsive phenotypes. Novel directions, including metabolic modulation, stromal reprogramming, and precision combination therapies, are discussed in the context of overcoming primary and acquired resistance. We highlight emerging biomarker strategies that integrate spatial transcriptomics to map immune exclusion zones, along with liquid biopsy monitoring of exosomal PD-L1 and circulating tumor DNA, to enable real-time adaptation of combination immunotherapy regimens.